Penerapan Metode Rca Untuk Menentukan Akar Penyebab Waste Pada Proses Pencucian Reaktor Dan Blending Tank Di Departemen Produksi 2 - Sri Lestari; Muhammad Yushiy Zahrowain; Zaenal Muttaqien (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2024)
This study aims to determine the root causes of waste in the reactor washing process and blending tank in the Department Production 2 PT. Pardic Jaya Chemicals which causes excessive costs or expenses if it is not identified what is the main cause of the problem. The research method used is root cause analysis (RCA) with Cause and EffectAnalysis or Fishbone Diagram. The results of the root cause research found several main factors, including differences in perception, limited tools, contaminated air and the character of the resin that was too solid. Proposed improvements to overcome this problem are by refreshing the work instructions, replacing the washing solvent with ethyl acetate by using distilled ethyl acetate (ETAC Ex-Dist) and adding N2 gas (Nitrogen) into the washing solvent.Â Keywords: Waste, Root Cause Analysis, Fishbone Diagram, proposed improvement plan, solvent